Procurement in short supply chains: Lessons learned from the tourism industry - Argyropoulou Maria; Argyropoulou Rachel; Folinas Dimitris; Misopoulos Fotios; Najacaj Suela (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This paper explores the procurement management strategies adopted in 100 five-star hotels operating in a highly touristic area in South Greece. The study identifies and discusses the benefits and the challenges of managing short supply chains in the selected region. Design/methodology/approach: Quantitative data were gathered by using a questionnaire with 16 closed-ended and 3 open-ended questions. The sample included the Managing Directors and some Administrators. The questionnaire was filled in between April 2017 and June of the same year. Findings: The majority of the respondents prefer to do business with local suppliers for a variety of reasons, the most important being the boost of local economy and immediate delivery which improves response time. High prices of local products and the availability of sufficient quantities were found the main concerns for the smooth running of operations. Research limitations/implications: The research uses data from two prefectures of Crete; a wider sample including other prefectures in Greece and in South Europe would provide a more holistic view on the effectiveness of short food supply chains. Originality/value: This paper makes a contribution by examining how short supply chains can be developed in local economies. This paper explores the procurement management strategies adopted in 100 five-star hotels operating in a highly touristic area in South Greece. The study identifies and discusses the benefits and the challenges of managing short supply chains in the selected region. The majority of the respondents prefer to do business with local suppliers for a variety of reasons, the most important being the boost of local economy and immediate delivery which improves response time. High prices of local products and the availability of sufficient quantities were found the main concerns for the smooth running of operations. Supplier selection criteria are also discussed.
Keywords: Z32; 330; Short Supply Chains; Hospitality industry; Sourcing; Greece